Validating a research professionalism model for faculty members at the Tabriz University of Medical Sciences: partial least squares structural equations modeling - Monireh Sabouri; Behnam Talebi; Zarrin Daneshvar Harris; Mahasti Alizadeh (Tabriz University of Medical Sciences, 2020)
Background: All researchers who carry out scientific research should consider the observance of research professionalism, which is indispensable. This study was carried out to validate a research professionalism model for faculty members at the Tabriz University of Medical Sciences. Methods: The research methods used in this study were applied in terms of the research purpose and survey for data collection. The statistical population consisted of all faculty members at the Tabriz University of Medical Sciences, of whom 16 individuals were selected through purposeful sampling for the qualitative section and 260 were selected through stratified random sampling for the quantitative section. Data gathering tools included interviews and questionnaires. Cronbach's alpha and content validity were used to determine the reliability and validity of the measurement tools. The grounded theory method was used to analyze the qualitative data, and structural equation modeling (PLS) was used for the quantitative data. Results: Research ethics model based on causal conditions, contextual and interventional factors, strategies, developing consequences and results of a first order factor analysis showed that the measurement models possessed composite reliability, divergent validity and convergent validity. The results of a second order factor analysis showed that structural models possessed an average or above coefficient of determination R² as well as an above-average Q2 prediction criterion. T values were significant (P>0.05). Goodness of fit (GOF) was 41 (not significant). Conclusion: The designed model shows both reliability and validity and an acceptable goodness of fit. Given the multidimensional nature of research professionalism, its promotion requires a systematic look at the foreground, concurrent events, consequences, and feedback on each dimension and related structures.